The Oxidized Low-Density Lipoprotein Receptor Mediates Vascular Effects of Inhaled Vehicle Emissions - Lund, Amie K. (American Thoracic Society, 2011)
Rationale: To determine vascular signaling pathways involved in inhaled air pollution (vehicular engine emission) exposure–induced exacerbation of atherosclerosis that are associated with onset of clinical cardiovascular events. Objectives: To elucidate the role of oxidized low-density lipoprotein (oxLDL) and its primary receptor on endothelial cells, the lectin-like oxLDL receptor (LOX-1), in regulation of endothelin-1 expression and matrix metalloproteinase activity associated with inhalational exposure to vehicular engine emissions. Methods: Atherosclerotic apolipoprotein E knockout mice were exposed by inhalation to filtered air or mixed whole engine emissions (250 μg particulate matter [PM]/m(3) diesel + 50 μg PM/m(3) gasoline exhausts) 6 h/d for 7 days. Concurrently, mice were treated with either mouse IgG or neutralizing antibodies to LOX-1 every other day. Vascular and plasma markers of oxidative stress and expression proatherogenic factors were assessed. In a parallel study, healthy human subjects were exposed to either 100 μg PM/m(3) diesel whole exhaust or high-efficiency particulate air and charcoal-filtered “clean” air (control subjects) for 2 hours, on separate occasions. Measurements and Main Results: Mixed emissions exposure increased oxLDL and vascular reactive oxygen species, as well as LOX-1, matrix metalloproteinase-9, and endothelin-1 mRNA expression and also monocyte/macrophage infiltration, each of which was attenuated with LOX-1 antibody treatment. In a parallel study, diesel exhaust exposure in volunteer human subjects induced significant increases in plasma-soluble LOX-1. Conclusions: These findings demonstrate that acute exposure to vehicular source pollutants results in up-regulation of vascular factors associated with progression of atherosclerosis, endothelin-1, and matrix metalloproteinase-9, mediated through oxLDL–LOX-1 receptor signaling, which may serve as a novel target for future therapy.